Edukasi, Pendampingan, dan Pemberdayaan Keluarga yang Menjalani Isolasi Mandiri COVID 19 dalam Upaya Peningkatan Status Kesehatan Keluarga: Education, Assistance, and Family Empowerment that are Understanding Self Isolation COVID 19 in the Effort Improvement of Family Health Status - Ulfah, Maria; Purwaningsih, Tinah; Utomo, Deddy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The beginning of 2020 was the beginning of the COVID-19 outbreak in the world; until 2021, more and more COVID-19 cases occurred in Indonesia, and more and more positive cases in the community resulted in hospitals not being able to accept patients for treatment in hospitals, so people who experienced moderate symptoms, mild and without symptoms can self-isolate in their respective homes. As of February 28, 2021, there were 2112 positive cases in Tegal City. During self-isolation, the patient needs family support; the family has a vital role in improving health status, so education, assistance, and empowerment are needed for families; education is provided through booklet media, as well as the provision of masks, hand sanitizers, hand soap, disinfectant spray and digital thermometer to families who are self-isolating. This activity aims to increase knowledge, attitudes, and behavior about COVID-19 to improve health status and prevent the spread of COVID-19 in the community, especially families.